Review of the book “Marxism, humanism and law: Althusser and Garaudy” by Juliana Paula Magalhães - Leite, Felipe Melonio (2019)
Review of the book “Marxism, humanism and law: Althusser and Garaudy” by Juliana Paula Magalhães Received: 01/23/2019Accepted: 06/28/2019